Effect of intraurethral papaverine on penile erection in rats - (:unkn) unknown (SPRINGER, 2004)
Objectives: The aim of this study is to investigate erectile response to intraurethral administration of papaverine in rats. Material and methods: Male Sprague-Dawley rats were used in this study. Under urethane anesthesia, penis was exposed and intracavernous pressure (ICP) was recorded through a 23-gauge needle, which was inserted into right corpus cavernosum. Effects of intraurethral application of incremental doses of 0.2 ml papaverine gel (4-17.5 mg) on intracavernosal pressure were observed and compared with those of 0.4 mg papaverine applied into corpus cavernosum. Mean arterial blood pressure (MABP) and heart rate were also monitored. Results: The mean basal ICP was 8.9 +/- 1.8 mm Hg. Intraurethral administration of papaverine did not increase ICP at any doses used in this study. After intracavernous injection of papaverine (0.4 mg), a significant increase in the ICP occurred from resting (8.9 +/- 1.8 mm Hg) to a peak at 57.5 +/- 9.9 mm Hg and persisted for 22.3 +/- 6.7 minutes (p < 0.05). The latter application significantly decreased MABP (22.3 +/- 3.1 mm Hg; p < 0.05). Conclusions: Intraurethral administration of papaverine does not seem to be an alternative to other erectile dysfunction treatment modalities. However, further studies on animals are necessary at higher concentrations or in combination with other mucosal enhancers to increase the effect of intraurethral administration of papaverine.
Keywords: Erection; Papaverine; Penis; Rat; Urethra